2018
DOI: 10.11607/jomi.5588
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy Analysis of the Adaptation of Single-Unit Screw-Retained Computer-Aided Design/Computer-Aided Manufacture Abutments After Mechanical Cycling

Abstract: Purpose: To measure the microgap between dental implants and custom abutments fabricated using different computer-aided design/computer-aided manufacture (CAD/CAM) methods before and after mechanical cycling. Materials and Methods: CAD software (Dental System, 3Shape) was used to design a custom abutment for a single-unit, screw-retained crown compatible with a 4.1-mm external hexagon dental implant. The resulting stereolithography file was sent for manufacturing using four CAD/CAM methods (n = 40): milling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…10A). This is also consistent with past reports which used the external joint system 18) . Zirconia is said to undergo sintering contraction as it is machined as semi-sintered blocks; these blocks are later subjected to a complete sintering in a high temperature furnace.…”
Section: Marginal Gapsupporting
confidence: 93%
See 2 more Smart Citations
“…10A). This is also consistent with past reports which used the external joint system 18) . Zirconia is said to undergo sintering contraction as it is machined as semi-sintered blocks; these blocks are later subjected to a complete sintering in a high temperature furnace.…”
Section: Marginal Gapsupporting
confidence: 93%
“…The marginal gap was measured by referring to past report 18) . The gap was captured at a magnification of 5,000 using a scanning electron microscope (SEM; SU6600, Hitachi, Tokyo, Japan) from a direction perpendicular to the long axis of the implant using the same platform, and the distance between the bottom edge of each abutment and the top edge of the implant was measured using a measuring tool in the SEM.…”
Section: Measurement Of Marginal Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental CAD/CAM systems allow the prosthetic seating interface to be milled directly onto the prosthetic structure or by cementing on prefabricated titanium‐based abutments . The cement on strategy combines the strength and fit precision of a titanium dental implant‐abutment interface with the esthetics of shaded custom‐milled ZO and results in low wear to prosthetic abutments . An intraoral cementation of titanium interfaces was chosen in the present patient, as the cement could minimize some misfit, creating an accommodation layer between Ti‐base and prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 studies measuring gap widths between OAs/NOAs and implants with an external connection, 4 studies found better precision of fit with OAs compared with NOAs. 1,[38][39][40] One study found that although the OAs statistically fit better than NOAs, both were within acceptable limits 33 ; 5 studies reported no differences between OAs and NOAs. 7,9,10,42,43 Two studies reported better fit when the NOAs were connected to the implants, compared with the OAs.…”
Section: Precision Of Fit At the Implant-abutment Interfacementioning
confidence: 99%